Health-related physical fitness indicators and clustered cardiometabolic risk factors in adolescents: A longitudinal study - Paula Roldão da Silva; Géssika Castilho dos Santos; Jadson Marcio da Silva; Waynne Ferreira de Faria; Raphael Gonçalves de Oliveira; Antonio Stabelini Neto (Elsevier, 2020)
Background/Objective: This study examined relationships between health-related physical fitness indicators and clustered cardiometabolic risk factors in adolescents between 2014 and 2017. Methods: The sample consisted of 93 students (60% girls), with complete data sets in both 2014 and 2017. The physical fitness components evaluated were: flexibility (sit and reach), muscular fitness (curl-up and push-up), cardiorespiratory fitness (progressive aerobic cardiovascular endurance run), and body fat (BMI). The cardiometabolic risk factors were: waist circumference, blood pressure, high-density lipoprotein cholesterol (HDL-C), triglycerides and fasting blood glucose. Z-scores were calculated for each risk factor, with the sum of risk factor z-scores values used to represent clustered cardiometabolic risk. Results: The results of cross-sectional analysis indicated that muscle fitness (curl-up: β = −0.37, p < 0.001; push-up: β = −0.38, p < 0.005) and cardiorespiratory fitness (β = −0.56, p < 0.001) were inversely associated with clustered cardiometabolic risk, with BMI positively associated (β = 0.58, p < 0.001). In the longitudinal analysis, cardiorespiratory fitness (β = −0.33; p < 0.005) and body fat (β = 0.46, p < 0.001) demonstrated a significant association with clustered cardiometabolic risk. However, no significant associations between the health-related physical fitness and clustered cardiometabolic risk were observed after adjustment for baseline values. Conclusion: Our cross-sectional findings highlight the importance of health-related physical fitness indicators to adolescents. In regarding the longitudinal analysis, further studies are needed in order to clarify the influence of physical fitness in the adolescence and cardiometabolic risk later in life.